Muskox and caribou adaptation to grazing on the Angujaartorfiup Nunaa range in West Greenland - Staaland, Hans; Olesen, Carsten Riis (Rangifer, 1992)
In recent years (1970-90) the caribou population of the Angujaartorfiup Nunaa range has decreased from about 40 000 animals to 2000. Overgrazing presumably depleted the lichen resources on the range during the population peak. At the same time altogether 27 muskoxen introduced in 1962 and 1965 have proliferated and the muskox population reached 3000 animals in 1990. At the present monocots dominate the diet for both species. The alimentary tract of both muskox and caribou collected in the fall of 1990 had characteristics of grazing ruminants, e.g. relatively small caecum-colon compared to total alimentary size and large alimentary fill relative to body weight. Caribou had an omasum comparable in size to the grazing Svalbard reindeer whereas the omasum of the muskoxen in size, resembled that of domestic cattle. Both winter and summer samples showed highest ruminal hemicellulose and cellulose concentrations in the muskoxen, whereas lignin and nitrogen were equal in the two species. Conclusively our data suggest adaptation to grazing in both species, but more so in muskoxen than in caribou.